2018
DOI: 10.1016/j.bbmt.2017.12.464
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Study of the Prebiotic Fructooligosaccharide in Allogeneic HCT and Evaluation of the Impact of This Compound on the Intestinal Microbiome

Abstract: Background: Limited data exists on the epidemiology and survival following central nervous system viral infections (CNS-VI) in allogeneic hematopoietic stem cell transplant (alloHCT) recipients. Methods: Querying the CIBMTR database, 165 alloHCT patients were reported to have a CNS virus isolated, within the first 6 months after HCT. Median age for this patient cohort was 43 years (range 1-76); and most patients were male (61%) and received myeloablative conditioning (65%) for malignant disease (87%) as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…One study evaluated the prebiotic, fructooligosaccharide (FOS), in 15 allogenic stem cell transplant patients and found that 4 of 5 patients tolerated the lower FOS dose of 5 g/day while 6 of 10 tolerated the higher dose of 10 g/day. 60 Although severe adverse events were not reported in this study, those who did not achieve 70% tolerability reported flatulence and discomfort. Additional studies are required to evaluate the efficacy, safety and tolerability of prebiotics and probiotics in the kidney transplant population.…”
Section: Therapeutic Opportunitiesmentioning
confidence: 61%
See 1 more Smart Citation
“…One study evaluated the prebiotic, fructooligosaccharide (FOS), in 15 allogenic stem cell transplant patients and found that 4 of 5 patients tolerated the lower FOS dose of 5 g/day while 6 of 10 tolerated the higher dose of 10 g/day. 60 Although severe adverse events were not reported in this study, those who did not achieve 70% tolerability reported flatulence and discomfort. Additional studies are required to evaluate the efficacy, safety and tolerability of prebiotics and probiotics in the kidney transplant population.…”
Section: Therapeutic Opportunitiesmentioning
confidence: 61%
“…The tolerability of prebiotics and probiotics in transplant populations has also not been adequately assessed. One study evaluated the prebiotic, fructooligosaccharide (FOS), in 15 allogenic stem cell transplant patients and found that 4 of 5 patients tolerated the lower FOS dose of 5 g/day while 6 of 10 tolerated the higher dose of 10 g/day . Although severe adverse events were not reported in this study, those who did not achieve 70% tolerability reported flatulence and discomfort.…”
Section: Therapeutic Opportunitiesmentioning
confidence: 83%